2021
DOI: 10.12973/ijem.7.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teachers' Views on Code-Switching as a Communicative Technique to Enhance the Teaching of Mathematics in Grade 4

Abstract: <p style="text-align: justify;">The teaching and learning of mathematics in South Africa are conducted through the authorised Language of Learning and Teaching (LoLT). South Africa has eleven official languages, and English is a Language of Learning and Teaching (LoLT) from the Intermediate and Further Education and Training (FET) Phase. This study explores teachers' views on code-switching as a communicative technique to enhance teaching mathematics in Grade 4 in selected primary schools in South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As has already been discussed, South Africa is a multilingual country, and as with any second language speakers elsewhere, a considerable proportion of students lack proficiency in English. Using home languages provides fringe benefits to students and educators who may have difficulties articulating concepts (Karakaya & Dikilitaş, 2020;Mawela & Mahlambi, 2021). Since English is a second language to many, the meanings of concepts often get lost in translation as students attempt to stay abreast with the pressures of academic life at universities, where they are suddenly confronted by a courseload that is taught and assessed in English (Du Plessis, 2021;Madadzhe, 2019;Vaccaro, 2022).…”
Section: Prominent Benefits Of Using Home Language As a Medium Of Ins...mentioning
confidence: 99%
“…As has already been discussed, South Africa is a multilingual country, and as with any second language speakers elsewhere, a considerable proportion of students lack proficiency in English. Using home languages provides fringe benefits to students and educators who may have difficulties articulating concepts (Karakaya & Dikilitaş, 2020;Mawela & Mahlambi, 2021). Since English is a second language to many, the meanings of concepts often get lost in translation as students attempt to stay abreast with the pressures of academic life at universities, where they are suddenly confronted by a courseload that is taught and assessed in English (Du Plessis, 2021;Madadzhe, 2019;Vaccaro, 2022).…”
Section: Prominent Benefits Of Using Home Language As a Medium Of Ins...mentioning
confidence: 99%
“…Therefore, this study aimed to explore teachers' perspectives and practices regarding code-switching. Instead of focusing on teachers' theoretical knowledge of code-switching, as most studies do (Mawela & Mahlambi, 2021), we observed their actual code-switching practices and asked about their perceptions of those practices. The study specifically focused on Geography teaching at the FET level (Grades 10-12).…”
Section: Introductionmentioning
confidence: 99%